Validation of the anxiety subscale of the Spanish version of the Edinburgh Postnatal Depression Scale (EPDS-A) - Gomà, Marta; Gordo, Leire; Cozodoy, Eric; Iriarte, Leire; Prims, Emma; Ferrer, Josep; Sánchez, Carmen; Llairó, Antònia; Arias-Pujol, Eulàlia (Frontiers in Psychiatry, 2023)
There is a need to implement routine perinatal mental health screening in Spain.Therefore, it is necessary to systematise the detection of depressive and anxious symptoms in pregnancy and postpartum using the same instrument. The Edinburgh Postnatal Stress Depression Scale (EPDS) is frequently used as a rapid, effective and cross-culturally validated screening tool for perinatal depression. In several countries, an Anxiety subscale, the EPDS-A, was identified within the EPDS. Although the factorial structure of the EPDS has been investigated in Spanish population, the EPDS-A has not yet been validated. This study aimed to validate the EPDS-A as a measure of perinatal anxiety in Spanish population.2 Methods: 161 women were evaluated with the EPDS and the State-Trait Anxiety Inventory (STAI) during pregnancy and postpartum. Confirmatory factor analysis (CFA) was used to confirm the trifactorial structure of the EPDS, comprising the dimensions of Depression, Anhedonia and Anxiety.Likewise, the invariance of the trifactorial model between pregnancy and postpartum was tested.Finally, the correlations between the EPDS-A and the STAI subscales (State Anxiety and Trait Anxiety) were calculated.The Exploratory factor analysis (EFA) driven three-factor structure of the EPDS, consisting of an Anhedonia factor (Items 1, 2 and 10), an Anxiety factor (Items 3, 4, 5 and 6) and a Depression factor (Items 7, 8 and 9), was the best measurement model for the current data compared to the alternative model tested [χ 2 = 34.592, df = 32, p = .34; χ 2 /df = 1.08; RMSEA = .023, 90% Confidence Interval [CI] [.000, .064], CFI = .996, GFI = .960). The model's invariance between pregnant and postpartum women was confirmed. The existence of an Anxiety subscale within the EPDS was also confirmed. The scores obtained with the EPDS-A correlated moderately with scores on both subscales of the STAI during pregnancy and after delivery. Using the STAI as a criterion and prioritising the instrument's sensitivity, a cut-off point of 4 points was established for the EPDS-A.Our results confirm the trifactorial structure of the EPDS in Spanish population. The Anxiety subscale was validated for routine perinatal mental health screening.